2012
DOI: 10.1161/circulationaha.111.084343
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Safety, and Therapeutic Efficacy of Human Induced Pluripotent Stem Cell-Derived Cardiomyocyte Sheets in a Porcine Ischemic Cardiomyopathy Model

Abstract: Background-Human induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) are a promising source of cells for regenerating myocardium. However, several issues, especially the large-scale preparation of hiPS-CMs and elimination of undifferentiated iPS cells, must be resolved before hiPS cells can be used clinically. The cell-sheet technique is one of the useful methods for transplanting large numbers of cells. We hypothesized that hiPS-CM-sheet transplantation would be feasible, safe, and therapeutically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
323
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 440 publications
(340 citation statements)
references
References 29 publications
7
323
0
3
Order By: Relevance
“…Recently, Templin et al (39) reported vascular differentiation and long-term engraftment of human iPSCs in a pig model of myocardial infarction. The use of human iPSC-derived cardiomyocyte sheets on temperature-sensitive polymers has been explored in the porcine ischemic model in an attempt to improve cell survival and engraftment (40). Additional technological improvements are required to obtain long-lasting therapeutic effects.…”
Section: Testing Ipscs In Animal Disease Modelsmentioning
confidence: 99%
“…Recently, Templin et al (39) reported vascular differentiation and long-term engraftment of human iPSCs in a pig model of myocardial infarction. The use of human iPSC-derived cardiomyocyte sheets on temperature-sensitive polymers has been explored in the porcine ischemic model in an attempt to improve cell survival and engraftment (40). Additional technological improvements are required to obtain long-lasting therapeutic effects.…”
Section: Testing Ipscs In Animal Disease Modelsmentioning
confidence: 99%
“…In this instance, the use of thermoreversible gel properties enables Lei and Schaffer (7) to simply change the temperature to quickly and efficiently extract cells from the gels without adversely affecting cell viability. The reversible use of the 3D hydrogel for hPSC growth is similar to the thermoreversible hydrogel surface-coating technologies pioneered by Okano and colleagues that are now being used to produce intact cell-sheet products for tissue-engineering applications (14).…”
Section: Manufacturing Considerationsmentioning
confidence: 97%
“…Additionally, adverse events including rhythm disturbances and teratoma/teratocarcinoma formation have been identified utilizing stem cell grafting techniques, hampering this methodology [29][30][31][32] .…”
Section: Figurementioning
confidence: 99%